Lewis-Sumner syndrome: subacute bilateral lesion of brachial plexus - Bunevičiūtė , R.; Masaitienė , R.; Klimašauskienė , A. (Neurologijos seminarai, 2018)
Lewis-Sumner syndrome (LSS) is a multifocal acquired demyelinating sensory and motor neuropathy considered as an asymmetric variant of chronic inflammatory demyelinating polyneuropathy affecting the upper and/or lower extremities. The most common clinical presentations of Lewis-Sumner syndrome are asymmetrical or multifocal sensory disturbances and weakness, electrophysiologically characterized by the presence of motor conduction blocks. In the case report, L-SS affected only the upper limbs, laboratory and electrophysiological testing was normal. Lewis-Sumner syndrome was diagnosed after brachial plexus magnetic resonance imaging. Since Lewis-Sumner syndrome is a rare disorder, its diagnosis and treatment are complicated as studies with a small number of patients and the results are often controversial.
Keywords: Lewis-Sumner syndrome; multifocal acquired demyelinating sensory and motor neuropathy; MADSAM